(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The study of English language dialects through linguistic theories provides valuable insights into the diversity and evolution of language. This paper examines key linguistic theories that explain the formation, variation, and development of English dialects, focusing on sociolinguistic, historical, and structural perspectives. Theories such as Labov’s variationist approach, which highlights the social factors influencing dialect variation, and the concept of dialectology, which maps regional linguistic differences, offer frameworks for understanding how English dialects emerge and persist. Additionally, the influence of historical events, language contact, and social change are explored within the context of the development of dialects. The paper also discusses the role of generative grammar and phonological theory in analyzing structural differences across dialects of English. By synthesizing these linguistic theories, the paper seeks to provide a comprehensive understanding of how English dialects reflect broader linguistic principles and societal dynamics, offering insights into both the diversity and unity of the English language.